PENDAMPINGAN PENINGKATAN MANJEMEN BUMDA DAN PENYUSUNAN DED (DETAIL ENGINEERING DRAWING) KANTOR PERBEKEL DESA SANUR KAJA BALI: Assistance In Improving BUMDA Management And Preparation Of DED (Detail Engineering Drawing) For The Village Perbekel Office Sanur Kaja Bali - Putra, Ida Bagus Udayana; Putra, Ida Bagus Gede Parama; Sulistiana, Putu Didik (Yayasan Al-Amin Qalbu, 2025)
This Community Service (PkM) activity aims to strengthen the institutional capacity of the Galang Kangin Traditional Village through two focus activities, namely mentoring the management of the Regional Owned Enterprise (BUMDA) and the preparation of the Detail Engineering Design (DED) for the construction of the Sanur Kaja Traditional Village Head Office. The main problems of the partners include limited institutional infrastructure, the absence of technical development documents, and weak organizational governance of the BUMDA. The implementation method includes field surveys, technical design, Focus Group Discussions (FGD), organizational management training, and simulation of office construction financing. The results of the activity show the preparation of a complete DED document and increased competence of BUMDA administrators in organizational and financial governance based on local potential. This program is an example of collaboration between academics and indigenous communities in realizing adaptive, professional, and sustainable institutional governance.